Radiosynthesis and Preliminary Biological Evaluation of [F]VC701, a Radioligand for Translocator Protein - Giuseppe Di Grigoli; Cristina Monterisi; Sara Belloli; Valeria Masiello; Letterio Salvatore Politi; Salvatore Valenti; Marco Paolino; Maurizio Anzini; Mario Matarrese; Andrea Cappelli; Rosa Maria Moresco (Molecular Imaging)
Positron emission tomography (PET) can be used to monitor in vivo translocator protein (TSPO) expression by using specific radioligands. Recently, several [ 11 C]PK11195 analogues have been synthesized to improve binding stability and brain availability. [ 18 F]VC701 was synthesized and validated in CD healthy rats by biodistribution and inhibition analysis. Imaging studies were also conducted on animals injected unilaterally in the striatum with quinolinic acid (QA) to evaluate the TSPO ligand uptake in a neuroinflammation/neurodegenerative model. [ 18 F]VC701 was synthesized with a good chemical and radiochemical purity and specific activity higher than 37 GBq/μmol. Kinetic studies performed on healthy animals showed the highest tracer biodistribution in TSPO-rich organs, and preadministration of cold PK11195 caused an overall radioactivity reduction. Metabolism studies showed the absence of radiometabolites in the rat brain of QA lesioned rats, and biodistribution analysis revealed a progressive increase in radioactivity ratios (lesioned to nonlesioned striatum) during time, reaching an approximate value of 5 4 hours after tracer injection. These results encourage further evaluation of this TSPO radioligand in other models of central and peripheral diseases.